An adaptation of the Lewis-Nielsen equations for the thermal conductivity of short fiber reinforced hybrid composites. (December 2019) - Ecke, Nicholas C.; Höller, Johannes; Niedermeyer, Jan; Klein, Peter; Schlarb, Alois K.
Abstract: Estimating the thermal conductivity of fiber reinforced plastics can be challenging, as they typically have anisotropic properties due to filler orientation during processing. Several analytical models for the thermal conductivity of multiphase materials are proposed in the literature. However, these are typically aimed at particulate fillers or fibers with an idealized orientation. In this work, the orthotropic thermal conductivity of multiphase compounds containing reinforcement fibers as well as different types of spherical particles were calculated using an analytical approach based on the Lewis-Nielsen model. The fiber orientation, which was determined from microsections, was converted into an orientational parameter that can be used within the Lewis-Nielsen set of equations. The results of this homogenization approach were compared to measurements. Good agreement between the model and the experimental results could be achieved for composites in which the reinforcing fibers are the dominant component influencing the thermal conductivity. For composites that comprise two strongly conductive components, the effective conductivity tends to be underestimated.